2011
DOI: 10.1111/j.1467-9817.2010.01486.x
|View full text |Cite
|
Sign up to set email alerts
|

One complicated extended family: the influence of alphabetic knowledge and vocabulary on phonemic awareness

Abstract: This research evaluated possible sources of individual differences in early explicit, smaller segment phonological awareness. In particular, the unique contributions of oral vocabulary and alphabetic knowledge to phonemic awareness acquisition were examined across the first year of school. A total of 57 participants were tested in kindergarten (mean age 5 years, 8 months) and again 1 year later midway through Grade 1. Results revealed that oral vocabulary and alphabetic knowledge were correlated with concurren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 34 publications
3
25
1
4
Order By: Relevance
“…With regard to Phonemic awareness, as mentioned by Silvén et al (2002) , this finding may support the assumption that conscious access to speech patterns is influenced, at least indirectly, by advances in implicit phonetic and phonotactic representations that can be related to language development during the 1st year of life. Ouellette and Haley (2013) stated that the principal motivation for considering the role of vocabulary in the emergence of phonemic awareness could be associated with the first words stored in mental lexicon. As new words are added, segmental representation becomes necessary so that similar sounding items are not confused with each other.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to Phonemic awareness, as mentioned by Silvén et al (2002) , this finding may support the assumption that conscious access to speech patterns is influenced, at least indirectly, by advances in implicit phonetic and phonotactic representations that can be related to language development during the 1st year of life. Ouellette and Haley (2013) stated that the principal motivation for considering the role of vocabulary in the emergence of phonemic awareness could be associated with the first words stored in mental lexicon. As new words are added, segmental representation becomes necessary so that similar sounding items are not confused with each other.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the 2nd factor was comprised the following tests: Phonemic Synthesis, Phonemic analysis, Rapid Naming Speed using pictures, and Reading of words and non-words. As described by Ouellette and Haley (2013) , phonemic awareness can also be categorized based on how it is being used. Specifically, explicit awareness at the level of the phoneme includes both analytic (ability to break a word down into constituent sounds) and synthetic skills (combining sounds together to make a larger segment, such as word).…”
Section: Discussionmentioning
confidence: 99%
“…We have found that the implemented program helped to increase the development of the different components of oral language (form, content and use), a fact highlighted as there are numerous studies indicating that written language is based on the domain of spoken language (Defior 2008;Ouellette and Haley, 2013;Guarneros and Vega, 2014), so that the higher the oral language level, the easier it will be to access the segmental units of spoken language and association of the phoneme-grapheme correspondence processes.…”
Section: Discussionmentioning
confidence: 99%
“…These are phonological awareness, letter-speech-sound processing and rapid automatized naming (RAN). Phonological awareness has been in the focus of much research as a key element in early literacy acquisition and an important and reliable predictor of later reading ability (Furnes & Samuelsson, 2011;Oulette & Haley, 2013;Shanahan, 2012). Phonological awareness is an umbrella term (Goswami & Bryant, 1990) used to refer to sensitivity to the sound structure of oral language and the ability to identify, discriminate and manipulate units of oral language (Sénéchal, Ouellette, & Young, 2004).…”
Section: The Activitymentioning
confidence: 99%
“…It develops from the ability to manipulate larger linguistic units (e.g., syllables) to eventual smaller phonological segment awareness (Carroll, Snowling, Hulme, & Stevenson, 2003;Ziegler & Goswami, 2005). Sensitivity to the smaller segments of individual speech sounds is referred to as phonemic awareness, distinguishing it from the more encompassing term, phonological awareness (Oulette & Haley, 2013). Phonemic awareness also encompasses "rudimentary phonological skills" (Anthony & Francis, 2005, p. 255), such as recognizing that two words rhyme and have a sound in common (Anthony & Francis, 2005;Goswami & Bryant, 1990).…”
Section: The Activitymentioning
confidence: 99%